Recruitment and retention: A randomized controlled trial of video-enhanced versus standard consent processes within the E-OPTIMAL study. (October 2019) - Brubaker, Linda; Jelovsek, J Eric; Lukacz, Emily S; Balgobin, Sunil; Ballard, Alicia; Weidner, Alison C; Gantz, Marie G; Whitworth, Ryan; Mazloomdoost, Donna
Background/aims: In this study, we compared two research consent techniques: a standardized video plus usual consent and usual consent alone. Methods: Individuals who completed 24-month outcomes (completers) in the Operations and Pelvic Muscle Training in the Management of Apical Support Loss study were invited to participate in an extended, longitudinal follow-up study (extended Operations and Pelvic Muscle Training in the Management of Apical Support Loss). Potential participants who were (1) able to provide consent and (2) not in long-term care facilities were randomized 1:1 to a standardized video detailing the importance of long-term follow-up studies of pelvic floor disorders followed by the usual institutional consent process versus the usual consent process alone. Randomization, stratified by site, used randomly permuted blocks. The primary outcome was the proportion of participants who enrolled in the extended study and completed data collection events 5 years after surgery. Secondary outcomes included the proportion enrolled in the extended study, completion of follow-up at each study year, completion of data collection points, completion of in-person visits, and completion of quality of life calls. Motivation and barriers to enrollment (study-level and personal-level) and satisfaction with the study consent process were measured by questionnaire prior to recruitment into extended Operations and Pelvic Muscle Training in the Management of Apical Support Loss. Groups were compared using an intention-to-treat principle, using unadjusted Student's t-test (continuous) and chi-square or Fisher's exact (categorical) test. A sample size of 340 (170/group) was estimated to detect a 15% difference in enrollment and study completion between groups with p < 0.05. Results: Of the 327 Operations and Pelvic Muscle Training in the Management of Apical Support Loss completers, 305 were randomized to the consent process study (153 video vs 152 no video). Groups were similar in demographics, surgical treatment, and outcomes. The overall rate of extended study enrollment was high, without significant differences between groups (video 92.8% vs no video 94.1%, p = 0.65). There were no significant differences in the primary outcome (video 79.1% vs no video 75.7%, p = 0.47) or in any secondary outcomes. Being "very satisfied" overall with study information (97.7% vs 88.5%, p = 0.01); "strong agreement" for feeling informed about the study (81.3% vs 70.8%, p = 0.06), understanding the study purpose (83.6% vs 71.0%, p = 0.02), nature and extent (82.8% vs 70.2%, p = 0.02), and potential societal benefits (82.8% vs 67.9%, p = 0.01); and research coordinator/study nurse relationship being "very important" (72.7% vs 63.4%, p = 0.03) were better in the video compared to the no video consent group. Conclusion: The extended study had high enrollment; most participants completed most study tasks during the 3-year observational extension, regardless of the use of video to augment research consent. The video was associated with a higher proportion of participants reporting improved study understanding and relationship with study personnel.